KRISIS KEMANUSIAAN DALAM DUNIA PENDIDIKAN MODERN: ANALISIS FILSAFAT HUMANISME SEBAGAI SOLUSI - Khanifah; Nurhaliza Anggraini; Nurul Mubin (JIP: Jurnal Ilmu Pendidikan, 2025)
Modern education has rapidly advanced in terms of technology, teaching strategies, and assessment frameworks. However, behind this progress lies a concerning humanitarian crisis. The decline of moral principles, loss of social empathy, and growing emphasis on materialism within the learning process indicate a distortion of education’s true purpose. This phenomenon is reflected in schools through cases of bullying, lack of respect for teachers, and intolerance among students. In this context, education should not only focus on academic achievement but also on shaping holistic human character. The philosophy of humanism offers a solution by asserting that humans must be the center of the educational process. Through a humanistic approach, education aims to cultivate self-awareness, empathy, and moral responsibility. Therefore, implementing humanistic values is essential to restore the fundamental purpose of education — humanizing humans and reinforcing universal humanitarian values amid the challenges of modernity.